INTERDISCIPLINARITY IN OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT: AN ANALYSIS OF THE TECHNICAL, ORGANIZATIONAL, AND SOCIAL DIMENSIONS OF OCCUPATIONAL RISKS - Viana, Rodrigo Cardoso; Méxas, Mirian Picinini (Seven Editora, 2026)
This chapter analyzes the importance of interdisciplinarity in Occupational Health and Safety (OHS) management, considering the technical, organizational, and social dimensions of occupational risks. It starts from the understanding that risks emerge from the interaction between technological systems, human behaviors, and organizational structures. A qualitative, exploratory, and descriptive approach is adopted, based on a literature review and normative documents, allowing the integration of different theoretical perspectives. In this context, interdisciplinarity is presented as a central element for overcoming fragmented approaches and for a systemic understanding of work. Its relationship with innovation is also discussed, highlighting the impact of new technologies and organizational changes. Finally, the importance of interdisciplinary training and strengthening a culture of prevention for safer and more sustainable work environments is emphasized.